2007
DOI: 10.1242/jcs.03258
|View full text |Cite
|
Sign up to set email alerts
|

Glycodelin-A interacts with fucosyltransferase on human sperm plasma membrane to inhibit spermatozoa-zona pellucida binding

Abstract: Journal of Cell Science 34 suggest that the glycodelin receptor(s) and zona pellucida glycoprotein receptor(s) are closely related. The objectives of this study were to identify the receptor of glycodelin-A in human spermatozoa and to characterize its interaction with human zona pellucida. Results Fucosyltransferase 5 (FUT5) is a sperm surface glycodelin-A binding proteinThe results of identification of glycodelin-A-bound sperm surface protein(s) are shown in Figs 1, 2. Sulfosuccinimidyl-2-[6-(biotinamido)-2-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 68 publications
0
37
0
2
Order By: Relevance
“…The receptor involved in this binding has been identified as fucosyltransferase 5 (FUT5) (70). The receptor binds competitively to both glycodelin-A and the zona pellucida glycoproteins.…”
Section: Fertilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The receptor involved in this binding has been identified as fucosyltransferase 5 (FUT5) (70). The receptor binds competitively to both glycodelin-A and the zona pellucida glycoproteins.…”
Section: Fertilisationmentioning
confidence: 99%
“…The receptor binds competitively to both glycodelin-A and the zona pellucida glycoproteins. Therefore, prior binding of glycodelin-A to FUT5 on a spermatozoon may occupy its binding site(s) of the zona pellucida glycoproteins and inhibit fertilisation unless glycodelin-A is transformed or removed (70) (Fig. 2).…”
Section: Fertilisationmentioning
confidence: 99%
“…Glycosylation of GdA is critical for the binding and biological activities of this glycoprotein in different cell types (2,(12)(13)(14). We demonstrated that non-glycosylated glycodelin has a minimal binding capacity and IL-6-inducing activity in monocytes/ macrophages.…”
Section: Discussionmentioning
confidence: 78%
“…Secretion-Sialylation mediates the binding and a number of biological activities of GdA in various cell types (2,(12)(13)(14). Here, we investigated the role of sialylation in GdA-induced IL-6 production in monocytes.…”
Section: Sialylation Of Gda Is Not Needed For Gda-induced Il-6mentioning
confidence: 99%
See 1 more Smart Citation